Upprepad administrering av trimetoprim/sulfadiazin till neonatala föl - Arnljot, Anna-Karin (2009)
Today most dosages used in horse medicine are based on studies in adult horses. Since there are differences between adult and neonatal horses with respect to different pharmacological parameters this can cause problems when administring drugs to neonatal foals. Neonatal sepsis is a common cause of morbidity and mortality in foals and aggressive antibiotic treatment is needed immediately when sepsis is suspected. In Sweden the combination of trimethoprim/sulphadiazine and bensylpenicillin is often used as the initial treatment. When administering drugs, interactions can occur between the drugs and endogenous substances. An example of such an interaction is called "displacement" and refers in this case to the competition for binding places on plasma proteins between drugs and highly protein-bound enogenous substances. Drugs that themselves are highly protein-bound are at a greater risk for displacement. Bilirubin is an example of an endogenous substance that to a great extent (>99 %) is bound to albumin. When displacement occur more free unconjugated bilirubin becomes available systemically and to a greater extent can pass the blood-brain barrier and cause cellular damage, so called kernicterus. Kernicterus has mostly been reported in neonatal children and is rarely seen in animals. Kernicterus in foals in association with trimethoprim/sulfadiazine treatment has not been reported but it is theoretically possible that also foals could be affected. The aims of the study were to evaluate the dosage used today and its safety with respect to displacement of bilirubin.